Socratic Path to Excellence - Pirc, Tadej (Anali PAZU HD, 2022)
I begin the article with a historical account of the School of Plato. First, I focus on the Academy as an institution and shed light on some of the key aspects of its operation, which are represented in Plato’s desire for cultivation and training in political affairs for the better future of society. Then I shortly present the organisational structure and the manner of the Socratic method of teaching and doing research under Plato’s leadership, founded on discussion. In the main part of the article I shift from the historical and methodological discussion to the normative explication of the teacher-student relationship and the encouragement of specific aptitudes as the focal approach for educational institutions of today. I strive to present this through Nietzsche’s critique of democratic educational institutions, which primarily seek the equity of formal education and common curriculum for all students, while there is little room left for excellence and the encouragement for specific aptitudes of students.
Keywords: Academy; Socratic method; Nietzsche; democracy; contemporary school; excellence